DFT Study of Binding and Electron Transfer from a Metal-Free Dye with Carboxyl, Hydroxyl, and Sulfonic Anchors to a Titanium Dioxide Nanocluster - Corneliu I. Oprea; Petre Panait; Jeanina Lungu; Daniela Stamate; Anca Dumbravă; Fanica Cimpoesu; Mihai A. Gîrţu (International Journal of Photoenergy)
We report results of density functional theory (DFT) calculations of a metal-free dye, 5-(4-sulfophenylazo)salicylic acid disodium salt, known as Mordant Yellow 10 (MY-10), used as sensitizer for TiO2 dye-sensitized solar cells (DSSCs). Given the need to better understand the behavior of the dyes adsorbed on the TiO2 nanoparticle, we studied various single and double deprotonated forms of the dye bound to a TiO2 cluster, taking advantage of the presence of the carboxyl, hydroxyl, and sulfonic groups as possible anchors. We discuss various binding configurations to the TiO2 substrate and the charge transfer from the pigment to the oxide by means of DFT calculations. In agreement with other reports, we find that the carboxyl group tends to bind in bidentate bridging configurations. The salicylate uses both the carboxyl and hydroxyl substituent groups for either a tridentate binding to adjacent Ti(IV) ions or a bidentate Ti-O binding together with an O-H-O binding, due to the rotation of the carboxyl group out of the plane of the dye. The sulfonic group prefers a tridentate binding. We analyze the propensity for electron transfer of the various dyes and find that for MY-10, as a function of the anchor group, the DSSC performance decreases in the order hydroxyl + carboxyl > carboxyl > sulfonate.